Skill acquisition of safe medication administration through realistic simulation: an integrative review - Breno de Sousa Santana; Alberto Augusto Martins Paiva; Marcia Cristina da Silva Magro
ABSTRACT Objective: to investigate evidence that indicates the contribution of realistic high, medium or low fidelity simulation to acquire knowledge, skills and attitudes in safe medication administration by nursing students. Methods: an integrative review of experimental studies from MEDLINE, LILACS, Web of Science, Scopus and Science Direct. The descriptors "nursing students", "simulation", "high fidelity simulation training", "medication errors" and "pharmacology" were used to identify 14 studies that answered the research question, and were assessed for accuracy methodological level and level of evidence. Results: there was a sample of quasi-experimental studies, (level 3 of evidence; 78.6%) and randomized clinical trials (level 2 of evidence; 21.4%), whose expressive majority showed superiority of the simulation strategy over the traditional methodology (71.4%). Conclusion: using low and high fidelity simulators, standardized patients and virtual simulation can promote acquisition of essential skills for patient safety.